Contain Multitudes: The Microbes Within US and a Grander View of Life - Ed Yong (London Vintage Publishing, 2016)
THE NEW YORK TIMES BESTSELLER FROM THE WINNER OF THE 2021 PULITZER PRIZE Your body is teeming with tens of trillions of microbes. It's an entire world, a colony full of life. In other words, you contain multitudes. They sculpt our organs, protect us from diseases, guide our behaviour, and bombard us with their genes. They also hold the key to understanding all life on earth. In I Contain Multitudes, Ed Yong opens our eyes and invites us to marvel at ourselves and other animals in a new light, less as individuals and more as thriving ecosystems. You'll never think about your mind, body or preferences in the same way again. 'Super-interesting... He just keeps imparting one surprising, fascinating insight after the next. I Contain Multitudes is science journalism at its best' Bill GatesSHORTLISTED FOR THE WELLCOME BOOK PRIZE 2017 SHORTLISTED FOR THE ROYAL SOCIETY SCIENCE BOOK PRIZE 2017
Keywords: Human body--Microbiology; Microorganisms; Symbiosis; Bacteria Anaerobic--physiology